Using and interpreting item analysis data... valuable tool in test construction. - Jenkins HM; Michael MM (Nurse Educator)
Construction of better test items in order to improve objective testing is a legitimate concern for nurse educators. Item analysis achieves this objective. This article focuses on the use and interpretation of item analysis data, both hand calculated and computer assisted. Improving the reliability of objective tests is one way of ensuring our accountability for student learning.